Correlation between leukocyte aggregation score of cerebrospinal fluid and bacterial meningitis in children - Meitha PE Togas; Nurhayati Masloman (Indonesian Pediatric Society, 2004)
Background Bacterial meningitis is one of life-threatening dis-eases and carries a risk of sequelae in affected children. In termsof cost and rapid differentiation between bacterial and non-bacte-rial meningitis, several tests have been proposed.Objective This study aimed to determine the use of leukocyteaggregation score (LAS) of cerebrospinal fluid (CSF) in diagnos-ing bacterial meningitis.Methods A prospective analytic study was done from October 2001to July 2002 in the Department of Child Health, Medical School,Sam Ratulangi University/ Manado General Hospital. Children pre-senting with symptoms of meningitis, aged between 28 days and13 years were enrolled. LAS was counted in percentage. Regres-sion analysis was used to determine the correlation between LASand diagnosis of bacterial meningitis.Results CSF examinations were done on 35 meningitis patients.Three patients were excluded. The remaining 32 patients com-prised of 11 with bacterial meningitis and the other 21 with non-bacterial meningitis. The mean of LAS in bacterial meningitis wassignificantly higher than that of non-bacterial meningitis (p<0.001).The cut off value of LAS to diagnose bacterial meningitis was12.35%.Conclusion LAS may be used as a fast and simple alternativediagnostic tool to confirm the diagnosis of bacterial meningitis